(untitled) (International Journal of Mathematics and Physics, 2013)
An electron drift in a monatomic gas was studied for a spatially uniform electric field. Functions of the electron energy distribution are found by solving the Boltzmann equation in the two-term approximation and applying the Monte Carlo method. We take into account both elastic and non-elastic collisions of electrons with atoms, recombination at the walls. Integral characteristics of the electron drift in the gas were calculated, allowing to analyze the drift of electrons on a qualitative level. The results of calculations of the energy balance of electrons and drift characteristics in argon are shown at the values of reduced field 1